Photocurable fluoropolyether elastomer composition and method for bonding same

By adding foaming inhibitors to the photocurable fluoropolyether-based elastomer composition and performing photocuring, the bubble problem caused by rapid curing in the photocurable fluoropolyether-based rubber composition is solved, and the substrate is realized at low temperature Quick bonding and high-strength curing with fluoroelastomers.

CN119391160APending Publication Date: 2025-02-07SHIN ETSU CHEMICAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411660266.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2019-11-11
Filing Date
2020-11-05
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

In the photocuring fluoropolyether rubber composition, the rapid curing property is preferred to cause bubbles to occur during curing after UV irradiation, which reduces the strength of the resin, and it is difficult to achieve substrate and cure in a short time under low temperature conditions. bonding of objects.

Method used

By adding foaming inhibitors to the photocurable fluoropolyether-based elastomer composition and photocuring under low temperature conditions, rapid bonding between the substrate and the fluoroelastomer is achieved while avoiding the generation of air bubbles in the resin.

Benefits of technology

The bonding between the substrate and the fluoroelastomer is achieved at a low temperature and a short time, and no bubbles are generated during the curing process, which improves the strength and bonding performance of the resin.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005143135070000031
    Figure BDA0005143135070000031
  • Figure BDA0005143135070000041
    Figure BDA0005143135070000041
  • Figure BDA0005143135070000042
    Figure BDA0005143135070000042
Patent Text Reader

Abstract

The invention provides a photocurable fluoropolyether elastomer composition and a bonding method thereof. The composition contains (A) 100 parts by mass of a linear polyfluorinated compound, (B) a fluorine-containing organohydrogenpolysiloxane, (C) a photoactive hydrosilylation reaction catalyst, and (D) 0.1-20 parts by mass of a zeolite. The component (A) has two or more alkenyl groups in one molecule and has a perfluoropolyether structure in the main chain, the component (B) has two or more hydrogen atoms bonded to silicon atoms in one molecule, the amount of the hydrogen atoms bonded to the silicon atoms in the component (B) is 0.5-3.0 moles per mole of the alkenyl groups in the component (A), and the amount of the component (C) is 0.5-3.0 moles per mole of the mass of the component (A). And the zeolite (D) has an average primary particle diameter of 30 [mu] m or less, and 0.1-500 ppm in terms of metal atoms.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the Chinese patent application with application number 202080078151.2, application date November 5, 2020, and invention name “Photocurable fluoropolyether elastomer composition and bonding method thereof”. Technical Field

[0002] The present invention relates to a photocurable fluoropolyether elastomer composition and a bonding method thereof. Background Art

[0003] In the past, curable fluorine-containing elastomer compositions utilizing the addition reaction of alkenyl and hydrosilyl groups upon heating are well known, and compositions that impart self-adhesive properties by adding an organopolysiloxane having a hydrosilyl group (SiH group) and an epoxy group and / or a trialkoxysilyl group as a third component have been proposed (Patent Documents 1 and 2). These can be cured by heating for a relatively short period of time, and the resulting cured product (fluorine-containing elastomer) is excellent in solvent resistance, chemical resistance, heat resistance, low temperature resistance, low moisture permeability, electrical properties, etc., and therefore, is used for bonding purposes in various industrial fields that require these properties. In particular, in the automotive industry, it is often used as an adhesive sealant for electrical components.

[0004] In recent years, from the viewpoint of energy saving and improving productivity, it is required to develop an elastomeric material that can be cured / bonded at a lower temperature and in a short time. However, if you want to obtain rapid curing in the above-mentioned thermosetting adhesive composition, you have to sacrifice storage stability and pot life. On the contrary, in order to ensure good storage stability and pot life, you have to sacrifice rapid curing. In addition, since the curing process and bonding process are undertaken in a single heat treatment, if you want to obtain adhesion between the cured product and the substrate under lower temperature conditions, it will take time in the curing process, and as a result, it is difficult to obtain curing and adhesion in a short time.

[0005] On the other hand, as an elastomer composition having excellent water and oil repellency, chemical resistance, etc., a photocurable fluoropolyether rubber composition comprising (A) a straight-chain fluoropolyether compound having at least two alkenyl groups and having a perfluoropolyether structure; (B) an organopolysiloxane having at least two mercapto groups and having a monovalent fluoroalkyl group or a monovalent fluoropolyether group; and (C) a photoinitiator has been developed, and is expected to be used as a coating material or a potting material for various electrical and electronic parts used in automobiles, chemical plants, inkjet printers, semiconductor production lines, etc. (Patent Document 3).

[0006] However, the above-mentioned photocurable fluoropolyether rubber composition is a material preferred for coating and potting various substrates because its cured product is in a gel or rubber state and is very soft. In addition, it has no adhesion to various substrates. However, it is difficult to use it in applications such as packaging materials, adhesive sealing materials, etc. that require adhesion to substrates and applications that require strength as an elastomeric material.

[0007] In view of this, a photocurable fluoroelastomer material has been proposed which has good storage properties and rapid curing properties at room temperature and exhibits adhesiveness at low temperatures in a short time (Patent Document 4).

[0008] Prior art literature

[0009] Patent Literature

[0010] [Patent Document] 1: Japanese Patent No. 3239717

[0011] [Patent Document] 2: Japanese Patent No. 3567973

[0012] [Patent Document] 3: Japanese Patent Publication No. 2007-106785

[0013] [Patent Document] 4: Japanese Patent Publication No. 2016-145354 Summary of the invention

[0014] Problem that the invention aims to solve

[0015] However, in a photocurable fluoropolyether rubber composition, if priority is given to rapid curing and thus adhesion in a short time, hydrogen generated by the dehydrogenation reaction of Si-H groups contained in the cross-linking agent during curing after UV irradiation will remain in the resin material as bubbles, causing a decrease in the strength of the resin.

[0016] Therefore, an object of the present invention is to provide a photocurable fluoropolyether elastomer composition and a bonding method thereof, wherein the photocurable fluoropolyether elastomer composition has good storage stability and rapid curing properties, can be bonded in a short time under low temperature conditions, and has the characteristics of not generating bubbles in the resin during curing.

[0017] Solutions for solving problems

[0018] The present inventors have gathered the results of intensive studies to solve the above-mentioned problems and have found that by applying a photocurable fluoropolyether elastomer composition to which a foaming inhibitor is added on the surface of a substrate and photocuring it, the substrate and the fluoroelastomer can be bonded at a low temperature and in a short time without generating bubbles in the resin, thereby completing the present invention.

[0019] That is, the present invention provides a photocurable fluoropolyether elastomer composition to which a foaming inhibitor is added and a bonding method thereof as described below. [1]

[0021] A photocurable fluoropolyether elastomer composition,

[0022] The invention comprises 100 parts by mass of a linear polyfluorinated compound (A), 0.5 to 3.0 parts by mass of a fluorinated organohydrogenpolysiloxane (B) in an amount of hydrogen atoms bonded to silicon atoms in the component (B) per 1 mol of alkenyl groups in the component (A), 0.1 to 500 ppm by mass of a photoactive hydrosilylation catalyst (C) in an amount calculated as metal atoms per the mass of the component (A), and 0.1 to 20 parts by mass of a zeolite (D).

[0023] The (A) linear polyfluoro compound has two or more alkenyl groups in one molecule and a perfluoropolyether structure in the main chain.

[0024] The (B) fluorinated organohydrogenpolysiloxane has two or more hydrogen atoms bonded to silicon atoms in one molecule, and

[0025] The (D) zeolite has an average primary particle size of 30 μm or less. [2]

[0027] The photocurable fluoropolyether elastomer composition according to [1], wherein

[0028] Component (A) is a linear fluoropolyether compound represented by the following formula (1),

[0029] CH2=CH-(X) g -Rf 1 -(X') g -CH=CH2 (1)

[0030] In formula (1), X is -CH2-, -CH2O-, -CH2OCH2- or -Y-NR 1 -CO-, where

[0031] Y is -CH2-, -Si(CH3)2CH2CH2CH2-, -Si(CH3)(CH=CH2)CH2CH2CH2-, -Si(CH=CH2)2CH2CH2CH2-, or o-silylphenylene, m-silylphenylene or p-silylphenylene represented by the following structural formula (Z), R 1 is a hydrogen atom or an unsubstituted or substituted monovalent hydrocarbon group,

[0032]

[0033] In formula (Z), R 3 and R 4 Each independently is -CH3 or -CH=CH2;

[0034] In formula (1), X' is -CH2-, -OCH2-, -CH2OCH2- or -CO-NR 2 -Y'-, wherein Y' is -CH2-, -CH2CH2CH2Si(CH3)2-, -CH2CH2CH2Si(CH3)(CH=CH2)-, -CH2CH2CH2Si(CH=CH2)2- or o-silylphenylene, m-silylphenylene or p-silylphenylene represented by the following structural formula (Z'), R 2 is a hydrogen atom or an unsubstituted or substituted monovalent hydrocarbon group,

[0035]

[0036] In formula (Z'), R 3’ and R 4’ Each independently is -CH3 or -CH=CH2;

[0037] In formula (1), g is independently 0 or 1;

[0038] In formula (1), Rf 1 is a divalent perfluoropolyether group represented by the following formula (i) or formula (ii),

[0039]

[0040] In formula (i), p and q are each 0 or an integer of 1 to 150, and the average value of the sum of p and q is 2 to 200, r is an integer of 0 to 6, t is 2 or 3,

[0041]

[0042] In formula (ii), u is an integer of 1 to 200, v is an integer of 1 to 50, and t is 2 or 3. [3]

[0044] The photocurable fluoropolyether elastomer composition according to [1] or [2], wherein

[0045] The present invention further contains 0.5 to 30 parts by mass of hydrophobic silica powder as the component (E) based on 100 parts by mass of the component (A). [4]

[0047] The photocurable fluoropolyether elastomer composition according to any one of [1] to [3], wherein

[0048] The present invention further contains, as component (F), an organohydrogensiloxane compound other than component (B) in an amount of 0.05 to 5.0 parts by mass based on 100 parts by mass of component (A), and the organohydrogensiloxane compound has one or more hydrogen atoms bonded to silicon atoms and epoxy groups and / or trialkoxysilyl groups bonded to silicon atoms via carbon atoms or carbon atoms and oxygen atoms in one molecule. [5]

[0050] The photocurable fluoropolyether elastomer composition according to any one of [1] to [4], wherein

[0051] The composition further contains a reaction control agent for the hydrosilylation reaction as the component (G). [6]

[0053] A method for bonding a substrate and a cured product of an elastomer composition, comprising the following steps:

[0054] The surface of the substrate is modified by plasma irradiation in advance, and the photocurable fluoropolyether elastomer composition described in any one of [1] to [5] is applied to the outer surface thereof, and the surface of the elastomer composition is irradiated with light to cure the elastomer composition, and the elastomer composition is allowed to stand at 10 to 120°C. [7]

[0056] The bonding method according to [6], wherein:

[0057] The substrate is metal, glass, ceramic or synthetic resin.

[0058] Effects of the Invention

[0059] According to the bonding method of the present invention, by applying a photocurable fluoropolyether elastomer composition to which a foaming inhibitor is added and photocuring it, a substrate and a fluorine-containing elastomer can be bonded at low temperature and in a short time without generating bubbles in the resin. DETAILED DESCRIPTION

[0060] Hereinafter, the present invention will be described in detail, but the present invention is not limited thereto.

[0061] [(A) Ingredient]

[0062] The linear polyfluoro compound of the component (A) in the photocurable fluoropolyether elastomer composition of the present invention is preferably a linear fluoropolyether compound represented by the above formula (1). It should be noted that the so-called "linear" in the present invention means that the fluorooxyalkylene groups of the repeating units constituting the main chain (fluoropolyether structure) of the polyfluoro compound are bonded to each other in a linear chain. Among them, the repeating units (fluorooxyalkylene groups) constituting the fluoropolyether structure themselves can be linear or branched (for example, perfluorooxy(methyl)methylene, perfluorooxy(methyl)ethylene, perfluorooxy(methyl)propylene, etc.).

[0063] Among them, R 1 and R 2 , preferably a hydrogen atom, a hydrocarbon group having 1 to 12 carbon atoms, particularly preferably 1 to 10. Specific examples of the hydrocarbon group include alkyl groups such as methyl, ethyl, propyl, butyl, hexyl, cyclohexyl, and octyl; aryl groups such as phenyl and tolyl; aralkyl groups such as benzyl and phenylethyl; or substituted monovalent hydrocarbon groups in which a part or all of the hydrogen atoms of these groups are substituted with halogen atoms such as fluorine.

[0064] Among them, Rf in formula (1) 1 It is a divalent perfluoropolyether group and is represented by the following formula (i) or formula (ii).

[0065]

[0066] (In formula (i), p and q are each 0 or an integer of 1 to 150, preferably an integer of 10 to 150, and the average value of the sum of p and q is 2 to 200, preferably 20 to 160. In addition, r is an integer of 0 to 6, preferably an integer of 0 to 4, and t is 2 or 3.)

[0067]

[0068] (In formula (ii), u is an integer of 1 to 200, preferably an integer of 20 to 160, v is an integer of 1 to 50, preferably an integer of 5 to 40, and t is 2 or 3.)

[0069] As Rf 1 Preferred examples include the following three groups (formula (i-1), formula (i-2) and formula (ii-1)). Among them, the divalent group having the structure of formula (i-1) listed first is particularly preferred.

[0070]

[0071] (In formula (i-1), p1 and q1 are integers of 1 to 150 respectively, and p1+q1 (average)=2 to 200. L is an integer of 2 to 6.)

[0072]

[0073] (In formula (i-2), p2 and q2 are integers of 1 to 150 respectively, and p2+q2 (average value) = 2 to 200. L is an integer of 2 to 6.)

[0074]

[0075] (In formula (ii-1), u1 is an integer from 1 to 200, and v1 is an integer from 1 to 50.)

[0076] Preferred examples of the component (A) include compounds represented by the following general formula (2).

[0077]

[0078] [In formula (2), X 1 Represents -CH2-, -CH2O-, -CH2OCH2- or -Y-NR 11 -CO-(Y represents the same group as above, R 11 is a hydrogen atom, a methyl group, a phenyl group or an allyl group), X 1’ -CH2-, -OCH2-, -CH2OCH2- or -CO-NR 12 -Y'-(R 12 Expressed as the same as the above R 11 The same group, Y' represents the same group as above), g is independently 0 or 1, L is an integer of 2 to 6, p3 and q3 are integers of 1 to 150, p3 + q3 (average value) = 2 to 200. ]

[0079] Specific examples of the linear fluoropolyether compound represented by the formula (1) include compounds represented by the following formulas.

[0080]

[0081] (In the formula, p' and q' are integers of 1 to 150, respectively, and p'+q' (average value) = 6 to 200)

[0082]

[0083] (In the formula, p' and q' are integers of 1 to 150, respectively, and p'+q' (average value) = 6 to 200.)

[0084]

[0085] (In the formula, p" and q" are each an integer of 1 to 150, and p"+q" (average value) = 2 to 200.)

[0086] The amount of alkenyl groups (especially alkenyl groups bonded to silicon atoms) contained in the straight-chain fluoropolyether compound represented by the above formula (1) is preferably 0.005 to 0.050 mol / 100 g, more preferably 0.007 to 0.040 mol / 100 g. If the amount of alkenyl groups contained in the straight-chain fluoropolyether compound is too small, the physical strength of the cured product may be reduced and / or no cured product may be obtained. In addition, if the amount of alkenyl groups contained in the straight-chain fluoropolyether compound is too large, the obtained cured product may become brittle and easily break.

[0087] It should be noted that the viscosity of the linear fluoropolyether compound of the above formula (1) (at 23°C) is preferably in the range of 100 to 100,000 mPa·s, more preferably in the range of 500 to 50,000 mPa·s, and further preferably in the range of 1,000 to 20,000 mPa·s. This is preferred because the resulting cured product has suitable physical properties even when the photocurable fluoropolyether elastomer composition is used for sealing, potting, coating, impregnation, etc. The linear fluoropolyether compound of formula (1) can be selected to have a preferred viscosity according to the intended use. In addition, a low-viscosity polymer and a high-viscosity polymer can be mixed to adjust the desired viscosity for use.

[0088] It should be noted that in the present invention, the viscosity is the viscosity measured by a rotational viscometer (e.g., BL type, BH type, BS type, cone and plate type, rheometer, etc.), and in particular, the viscosity (at 23°C) of the linear fluoropolyether compound represented by the above formula (1) is the viscosity measured in accordance with JIS K7117-1. In addition, the degree of polymerization (or molecular weight) of the linear fluoropolyether compound, which is reflected by the number of repetitions of the perfluorooxyalkylene unit constituting the perfluoropolyether structure of the main chain, is determined as the number average degree of polymerization (or number average molecular weight) in terms of polystyrene in gel permeation chromatography (GPC) analysis using a fluorine-based solvent as a developing solvent.

[0089] Furthermore, in order to adjust the linear fluoropolyether compound of the above formula (1) to a number average molecular weight required for the purpose, the linear fluoropolyether compound as described above can be subjected to a hydrosilylation reaction with an organic silicon compound containing two hydrosilyl groups (Si—H groups) in the molecule in advance under conventional methods and conditions, and the chain-extended product can be used as the component (A).

[0090] These linear fluoropolyether compounds may be used alone or in combination of two or more.

[0091] The content of the linear polyfluorinated compound of component (A) having two or more alkenyl groups in one molecule and a perfluoropolyether structure in the main chain in the composition is preferably 50 to 99 mass %, particularly preferably 70 to 95 mass %, further preferably 80 to 95 mass %.

[0092] [Ingredient (B)]

[0093] The component (B) is a fluorine-containing organohydrogenpolysiloxane having 2 or more, preferably 3 to 50, hydrogen atoms bonded to silicon atoms (i.e., hydrosilyl groups represented by Si-H) in one molecule. The component (B) acts as a crosslinking agent and / or chain extender for the above-mentioned component (A). In addition, from the viewpoints of compatibility with the component (A), dispersibility, uniformity after curing, etc., it is a fluorine-containing organic group having one or more, preferably 1 to 10, in one molecule. It is preferred that the fluorine-containing organic group has one or more fluorine-containing groups such as monovalent perfluoroalkyl, monovalent perfluorooxyalkyl, divalent perfluoroalkylene or divalent perfluorooxyalkylene in one molecule.

[0094] Examples of the monovalent or divalent fluorine-containing organic group include a perfluoroalkyl group, a perfluorooxyalkyl group, a perfluoroalkylene group, and a perfluorooxyalkylene group represented by the following formula.

[0095] C g F 2g+1 -

[0096] -C g F 2g -

[0097] (In the formula, g is an integer of 1 to 20, preferably an integer of 2 to 10.)

[0098]

[0099] (In the formula, f is an integer of 1 to 200, preferably an integer of 1 to 100, and h is an integer of 1 to 3.)

[0100]

[0101] (In the formula, i and j are each an integer greater than or equal to 1, preferably an integer from 1 to 100, and the average value of i+j is from 2 to 200, preferably from 2 to 100.)

[0102] (CF2O) d -(CF2CF2O) e -CF2-

[0103] (In the formula, d and e are each an integer of 1 to 50, preferably an integer of 1 to 40.)

[0104] In addition, it is preferred that these perfluoroalkyl, perfluorooxyalkyl, perfluoroalkylene or perfluorooxyalkylene groups are bonded to silicon atoms via divalent linking groups. The divalent linking groups may be alkylene groups, arylene groups and combinations thereof, or groups formed by interposing ether bonds (oxygen atoms), amide bonds, carbonyl bonds, ester bonds, diorganosilylene groups and the like into these groups, for example, the following divalent linking groups having 2 to 13 carbon atoms may be listed, but are not limited thereto.

[0105] -CH2CH2-

[0106] -CH2CH2CH2-

[0107] -CH2CH2CH2OCH2-

[0108] -CH2CH2CH2-NH-CO-

[0109] -CH2CH2CH2-N(Ph)-CO-

[0110] -CH2CH2CH2-N(CH3)-CO-

[0111] -CH2CH2CH2-N(CH2CH3)-CO-

[0112] -CH2CH2-Si(CH3)2-Ph'-N(CH3)-CO-

[0113] -CH2CH2CH2-Si(CH3)2-Ph'-N(CH3)-CO-

[0114] -CH2CH2CH2-O-CO-

[0115] (In the formula, Ph is a phenyl group and Ph' is a phenylene group.)

[0116] Examples of the monovalent substituents bonded to silicon atoms other than the monovalent or divalent fluorinated organic groups and hydrogen atoms bonded to silicon atoms in the fluorinated organohydrogenpolysiloxane of the component (B) include alkyl groups such as methyl, ethyl, propyl, butyl, hexyl, cyclohexyl, octyl and decyl; alkenyl groups such as vinyl and allyl; aryl groups such as phenyl, tolyl and naphthyl; aralkyl groups such as benzyl and phenethyl; and unsubstituted or substituted monovalent hydrocarbon groups having 1 to 20 carbon atoms, preferably 1 to 12 carbon atoms, in which some or all of the hydrogen atoms of these groups are substituted with chlorine atoms, cyano groups or the like, for example, chloromethyl, chloropropyl and cyanoethyl groups.

[0117] The fluorinated organohydrogenpolysiloxane as component (B) may be any one of cyclic, linear, branched, three-dimensional network and combinations thereof. The number of silicon atoms in the fluorinated organohydrogenpolysiloxane is not particularly limited, but is generally about 2 to 60, preferably about 3 to 30.

[0118] As the component (B) having a monovalent or divalent fluorine-containing organic group and a hydrogen atom bonded to a silicon atom, for example, the following compounds can be cited. These compounds can be used alone or in combination of two or more. It should be noted that in the following formula, Me represents a methyl group and Ph represents a phenyl group.

[0119]

[0120]

[0121]

[0122]

[0123]

[0124]

[0125]

[0126]

[0127] The amount of Si-H groups contained in the fluorinated organic hydrogen polysiloxane of the above-mentioned component (B) is preferably 0.00050 to 0.01000 mol / g, more preferably 0.00100 to 0.00800 mol / g. If the amount of Si-H groups contained in the fluorinated organic hydrogen polysiloxane is too small, the crosslinking density may become insufficient and the physical properties of the obtained cured product may be reduced. In addition, if the amount of Si-H groups contained in the fluorinated organic hydrogen polysiloxane of the component (B) is too large, foaming may occur during curing and / or the physical properties of the obtained cured product may change significantly over time.

[0128] These fluorinated organohydrogenpolysiloxanes may be used alone or in combination of two or more.

[0129] The amount of the above-mentioned component (B) is 0.5 to 3.0 moles of the hydrosilyl group, i.e., the Si-H group, in the component (B) relative to 1 mole of the alkenyl group such as the vinyl group, the allyl group, and the cycloalkenyl group contained in the component (A), and is particularly preferably 0.8 to 2.0 moles. If the hydrosilyl group (≡Si-H) is too little, the crosslinking density becomes insufficient, and a cured product may not be obtained. In addition, if the hydrosilyl group (≡Si-H) is too much, foaming may occur during curing.

[0130] The fluorinated organohydrogenpolysiloxane of the component (B) does not contain an epoxy group or a trialkoxysilyl group in the molecule, and thus is clearly distinguished from the organohydrogensiloxane which is the adhesion improver of the component (F) described later.

[0131] 〔(C) ingredient〕

[0132] Component (C) is a photoactive hydrosilylation catalyst. The photoactive hydrosilylation catalyst is a catalyst that is activated by light irradiation, especially by irradiation with ultraviolet rays at 300 to 400 nm, thereby promoting the addition reaction of the alkenyl group in component (A) and the hydrosilyl group in component (B). The photoactive hydrosilylation catalyst mainly includes platinum group metal catalysts and nickel group metal catalysts. As platinum group metal catalysts, platinum group metal complex compounds, palladium group metal complex compounds and rhodium group metal complex compounds can be listed; as nickel group metal catalysts, nickel group metal complex compounds, iron group metal complex compounds and cobalt group metal complex compounds can be listed. Among them, platinum group metal complex compounds are easier to obtain and show good catalytic activity, so they are preferred.

[0133] As photoactive platinum metal complex compounds, there are, for example, (η 5-cyclopentadienyl)tri(σ-alkyl)platinum complex or β-diketonate platinum complex. Specifically, (methylcyclopentadienyl)trimethylplatinum(IV), (cyclopentadienyl)trimethylplatinum(IV), (1,2,3,4,5-pentamethylcyclopentadienyl)trimethylplatinum(IV), (cyclopentadienyl)dimethylethylplatinum(IV), (cyclopentadienyl)dimethylacetylplatinum(IV), (trimethylsilylcyclopentadienyl)trimethylplatinum(IV), (methoxycarbonylcyclopentadienyl)trimethylplatinum(IV), (dimethylphenylsilylcyclopentadienyl)trimethylcyclopentadienylplatinum(IV) bis(1-phenyl-1,3-butanedione)platinum(II), bis(1,3-diphenyl-1,3-propanedione)platinum(II) and bis(hexafluoroacetylacetonate)platinum(II).

[0134] When these catalysts are used, they may be used in a solid state if they are solid catalysts. However, in order to obtain a more uniform cured product, it is preferred to use a mixed solution of the catalyst dissolved in a suitable solvent and compatible with the fluoropolyether compound of the component (A).

[0135] There is no particular limitation on the type of solvent used, as long as it can dissolve the catalyst. However, it is more preferred to use a solvent in which a portion of the hydrogen atoms of the hydrocarbon group are replaced by fluorine, or a mixed solvent of a solvent in which a portion of the hydrogen atoms of the hydrocarbon group are replaced by fluorine and a solvent in which all the hydrogen atoms of the hydrocarbon group are replaced by fluorine, because it has the advantage of being able to more uniformly disperse the catalyst in the composition.

[0136] As solvents in which a part of hydrogen in the hydrocarbon group is replaced by fluorine, there can be mentioned, for example, 1,3-bis(trifluoromethyl)benzene, 1,2-bis(trifluoromethyl)benzene, 1,4-bis(trifluoromethyl)benzene, 1-methyl-3-(pentafluoroethyl)benzene, 1,1,1-trifluoro-3-[3-(trifluoromethyl)phenyl]propan-2-one, methyl 4-fluoro-3-(trifluoromethyl)benzoate, n-butyl heptafluorobutyrate, ethyl 3,5-bis(trifluoromethyl)benzoate, 2-methyl-5-(trifluoromethyl)benzaldehyde and 2,3-dimethoxytrifluorotoluene.

[0137] Examples of the solvent in which all hydrogen atoms of the hydrocarbon group are replaced by fluorine atoms include octafluorotoluene, (1,1,2,3,3,3-hexafluoropropoxy)perfluorobenzene, pentafluoroethyl 2,2,2-trifluoroethyl ether, Fluorinert (manufactured by 3M Co.), PF5060 (manufactured by 3M Co.), and perfluoropolyether oligomers.

[0138] When the catalyst is used as a solution, the preferred mixing ratio of the linear polyfluoro compound of component (A) and the catalyst solution is in the range of 100:0.01 to 1.00 (mass ratio). When the amount of the catalyst solution is greater than this range, the physical properties of the cured product may be affected; on the other hand, when the amount of the catalyst solution is less than this range, poor dispersion of the composition may occur. Therefore, it is advisable to appropriately adjust the concentration of the catalyst solution so that it is within the range of this mixing ratio.

[0139] The amount of component (C) used is 0.1 to 500 ppm, particularly preferably 1 to 100 ppm, calculated as the mass of metal atoms relative to component (A). If the amount of component (C) used is too small, the photocurable composition may not be able to obtain sufficient photocurability. On the other hand, if the amount of component (C) used is too large, it may cause an adverse effect on the heat resistance of the cured product.

[0140] [Ingredient (D)]

[0141] The zeolite of the component (D) is a crystalline zeolite and has fine pores at the molecular diameter level, and has the characteristic of suppressing foaming in the system by absorbing micromolecules in the pores. In the present invention, the component (D) is an essential component and is added to the composition in advance. After the composition is UV-irradiated, the hydrogen generated by the dehydrogenation reaction from the component (B) is captured while maintaining good curability / adhesion, thereby obtaining a good cured product without foaming in the composition.

[0142] Zeolite is a general term for aluminosilicate, aluminophosphate or silicoaluminophosphate, and there are various grades according to the size of its pores. From the viewpoint of adsorbing hydrogen generated by dehydrogenation, 3A grade aluminosilicate or 4A grade aluminosilicate (pore diameter is 0.14 mm / s) is preferred. A-type zeolite or pore size A-type zeolite), but is not limited thereto.

[0143] In order to obtain a room temperature curable fluoropolyether composition capable of suppressing foaming without impairing the conventional curing characteristics and physical properties after curing, the average primary particle size of the zeolite of the component (D) needs to be 30 μm or less, and particularly preferably 15 nm to 20 μm. If the average primary particle size of the zeolite is larger than 30 μm, the light transmittance to a deep part during UV irradiation is reduced, which may cause an adverse effect on the physical properties after curing.

[0144] (D) The average primary particle size of the component is obtained by measuring the particle size of 30 or more primary particles selected at random and averaging (number average) the particle size of the 30 or more primary particles when observing the particles by a scanning electron microscope (SEM). In this case, the particle size is the diameter (circle equivalent diameter) of a circle having an area equal to the projected area of ​​the particle.

[0145] The amount of component (D) is 0.1 to 20 parts by mass, preferably 0.5 to 10 parts by mass, relative to 100 parts by mass of component (A). If the amount of component (D) is less than this amount, it is not suitable for providing good foaming suppression; on the contrary, if it is increased, it will increase the viscosity, poor workability, and adversely affect the physical properties after curing.

[0146] [Ingredient (E)]

[0147] The hydrophobic silica powder of the component (E) is an optional component that can be added to the composition of the present invention as needed, and has the function of imparting appropriate physical strength to the cured product obtained from the photocurable fluoropolyether elastomer composition, and also has the function of uniformly dispersing the organohydrogensiloxane of the component (F) described later in the composition. The hydrophobic silica powder of the component (E) is a well-known filler for silicone rubber with a BET specific surface area of ​​50 m 2 / g or more, especially 50 to 400 m 2 / g of fine powdered silica subjected to hydrophobic treatment is preferred.

[0148] Examples of fine powder silica include fumed silica (fumed silica or dry silica), precipitated silica (wet silica), and colloidal silica. Among them, fumed silica is particularly preferred.

[0149] The BET surface area is less than 50 m 2 / g, the physical strength of the obtained solidified product may be insufficient, and the (F) component may not be evenly dispersed. In addition, if the BET specific surface area is greater than 400m 2 / g, the kneading operation may become difficult and the dispersion of the (E) component itself may become uneven. It should be noted that the BET specific surface area in the present invention can be measured in accordance with the DIN 66131 standard.

[0150] Examples of the hydrophobic treatment agent for the fine powder silica include organochlorosilane, organodisilazane, cyclic organopolysilazane, and linear organopolysiloxane, among which organochlorosilane, organodisilazane, and cyclic organopolysilazane are preferred.

[0151] When the component (E) is added to the composition of the present invention, the amount of the component (E) is preferably 0.5 to 30 parts by mass, more preferably 1 to 25 parts by mass, relative to 100 parts by mass of the component (A). If the amount of the component (E) is less than 0.5 parts by mass, the effect of adding the component (E) may not be obtained; on the other hand, if the amount of the component (E) is more than 30 parts by mass, the fluidity of the composition may be deteriorated, and the curing property by light may also be significantly reduced.

[0152] 〔(F)Component〕

[0153] The organohydrogensiloxane of the component (F) is an arbitrary component that can be added to the composition of the present invention as needed, and is a component used as an adhesive imparting agent for improving the adhesion of the cured product formed by curing the composition of the present invention to various substrates. Such an organohydrogensiloxane of the component (F) is an organohydrogensiloxane having one or more hydrogen atoms bonded to silicon atoms, and epoxy groups and / or trialkoxysilyl groups bonded to silicon atoms through carbon atoms or carbon atoms and oxygen atoms in one molecule, preferably further having one or more monovalent perfluoroalkyl groups or monovalent perfluorooxyalkyl groups bonded to silicon atoms through divalent linking groups containing carbon atoms bonded to silicon atoms or carbon atoms and oxygen atoms. It should be noted that the component (F) is clearly distinguished from the above-mentioned component (B) in that it is necessary to contain epoxy groups and / or trialkoxysilyl groups in the molecule.

[0154] The siloxane skeleton of such an organohydrogensiloxane may be any of cyclic, chain, branched, etc., and may be a mixture of these.

[0155] Specifically, as the component (F), a component represented by the following average composition formula can be used.

[0156]

[0157] (In the formula, R 5 are independently unsubstituted or halogen-substituted monovalent hydrocarbon groups, and A and B are represented as follows. w represents 0≤w≤100, x represents 1≤x≤100, y represents 1≤y≤100, and z represents 0≤z≤100. )

[0158] As R 5The monovalent hydrocarbon group substituted or unsubstituted with halogen is preferably a hydrocarbon group having 1 to 10 carbon atoms, and particularly preferably a hydrocarbon group having 1 to 8 carbon atoms. Specifically, alkyl groups such as methyl, ethyl, propyl, butyl, hexyl, cyclohexyl, and octyl; aryl groups such as phenyl and tolyl; aralkyl groups such as benzyl and phenylethyl; or substituted monovalent hydrocarbon groups in which a part or all of the hydrogen atoms of these groups are substituted with halogen atoms such as fluorine. Among them, methyl is particularly preferred.

[0159] w is preferably 0≤w≤20, x is preferably 1≤x≤20, y is preferably 1≤y≤20, z is preferably 1≤z≤20, and 3≤w+x+y+z≤50 is preferred.

[0160] A represents an epoxy group and / or trialkoxysilyl group bonded to a silicon atom via a carbon atom or a carbon atom and an oxygen atom, and specific examples thereof include the following groups.

[0161]

[0162] [In the formula, R 6 It represents a divalent hydrocarbon group (such as an alkylene group and a cycloalkylene group) having 1 to 10 carbon atoms, particularly 1 to 5 carbon atoms, which may have an oxygen atom interposed therein.]

[0163] -R 7 -Si(OR 8 )3

[0164] [In the formula, R 7 represents a divalent hydrocarbon group (such as an alkylene group) having 1 to 10 carbon atoms, particularly 1 to 4 carbon atoms, R 8 It represents a monovalent hydrocarbon group (alkyl group, etc.) having 1 to 8 carbon atoms, particularly 1 to 4 carbon atoms.]

[0165]

[0166] [In the formula, R 9 represents a monovalent hydrocarbon group (such as an alkyl group) having 1 to 8 carbon atoms, particularly 1 to 4 carbon atoms, R 10 represents a methyl group or an ethyl group, and k represents an integer from 2 to 10.]

[0167] B represents a monovalent perfluoroalkyl group or perfluorooxyalkyl group bonded to a silicon atom via a carbon atom or a carbon atom and an oxygen atom. Examples of the monovalent perfluoroalkyl group or perfluorooxyalkyl group include groups represented by the following general formula.

[0168] C g’ F 2g’+1 -

[0169] (In the formula, g' is an integer of 1 to 20, preferably an integer of 2 to 10.)

[0170] F-[CF(CF3)CF2O] f’ -C h’ F 2h’ -

[0171] (In the formula, f' is an integer of 2 to 200, preferably an integer of 2 to 100, and h' is an integer of 1 to 3.)

[0172] The divalent linking group containing carbon atoms or carbon atoms and oxygen atoms may be an alkylene group, an arylene group, and a combination thereof, or a linking group in which an ether bond oxygen atom, an amide bond, a carbonyl bond, etc. are interposed between these groups. For example,

[0173] -CH2CH2-

[0174] -CH2CH2CH2-

[0175] -CH2CH2CH2OCH2-

[0176] -CH2CH2CH2-NH-CO-

[0177] -CH2CH2CH2-N(CH3)-CO-

[0178] -CH2CH2CH2-N(Ph)-CO-

[0179] (However, Ph is phenyl.) It is a divalent linking group having 2 to 12 carbon atoms.

[0180] These organohydrogensiloxanes can be obtained by adding a compound containing an aliphatic unsaturated group such as a vinyl group, an allyl group, and an epoxy group and / or a trialkoxysilyl group to an organohydrogensiloxane having three or more hydrogen atoms bonded to a silicon atom (Si-H group) in one molecule. In addition, as required, a compound containing an aliphatic unsaturated group and a perfluoroalkyl group or a perfluorooxyalkyl group can also be subjected to a partial addition reaction according to a conventional method to obtain the organohydrogensiloxane. It should be noted that the number of the above-mentioned aliphatic unsaturated groups is less than the number of Si-H groups.

[0181] When producing the organohydrogensiloxane, the target product may be isolated after the reaction is completed, or a mixture from which only unreacted products and the addition reaction catalyst have been removed may be used.

[0182] Specific examples of the organopolysiloxane of the component (F) include organopolysiloxanes represented by the following structural formulas. In the following formula, Me is a methyl group, and Ph is a phenyl group.

[0183]

[0184]

[0185] (o, q, r are positive integers, and p is an integer greater than 0.)

[0186]

[0187]

[0188] (o, q, r are positive integers, and p is an integer greater than 0.)

[0189]

[0190] (F) The component may be used alone or in combination of two or more.

[0191] When the component (F) is incorporated into the composition of the present invention, the amount of the component (F) used is in the range of 0.05 to 5.0 parts by mass, preferably in the range of 0.1 to 3.0 parts by mass, relative to 100 parts by mass of the component (A). When the amount is less than 0.05 parts by mass, the effect of incorporating the component may not be obtained, and when the amount exceeds 5.0 parts by mass, the fluidity of the composition may deteriorate, the physical strength of the obtained cured product may be reduced, and curing may be hindered.

[0192] In addition, the total molar ratio of the hydrosilyl groups (Si-H groups) contained in the entire composition to the total alkenyl groups bonded to silicon atoms contained in the entire composition (particularly the alkenyl groups bonded to silicon atoms in the (A) component), and in particular the total molar ratio of the Si-H groups in the (B) components and the (F) components to the alkenyl groups bonded to silicon atoms in the (A) component (Si-H groups / alkenyl groups), is preferably 0.5 to 3.0 mol / mol, and particularly preferably 0.8 to 2.0 mol / mol. If the amount of the hydrosilyl groups (Si-H groups) contained in the entire composition is less than the above molar ratio, the crosslinking density may be insufficient, and a cured product may not be obtained, and the desired adhesiveness may not be obtained. On the contrary, if the amount of the hydrosilyl groups (Si-H groups) contained in the entire composition is greater than the above molar ratio, foaming due to the dehydrogenation reaction may increase, and a cured product with a smooth surface may not be obtained.

[0193] [(G) ingredient]

[0194] The reaction control agent of the hydrosilylation reaction of the component (G) is an arbitrary component that can be formulated into the composition of the present invention as needed. Here, examples of the reaction control agent of the component (G) include, for example, 1-ethynyl-1-hydroxycyclohexane, 3-methyl-1-butyn-3-ol, 3,5-dimethyl-1-hexyn-3-ol, 3-methyl-1-pentene-3-ol, phenylbutynol and other acetylenic alcohols; 3-methyl-3-pentene-1-yne, 3,5-dimethyl-3-hexene-1-yne and other acetylenic compounds; fluorine-containing acetylenic alcohol compounds represented by the following structural formula; polymethylvinylsiloxane cyclic compounds and organic phosphorus compounds, etc.

[0195]

[0196]

[0197]

[0198] When using these reaction control agents, substances dissolved in appropriate solvents such as toluene may also be used. In addition, since these reaction control agents have different control capabilities depending on their chemical structures, the amounts of these reaction control agents should be adjusted to very suitable amounts. Generally, if the amount of the reaction control agent is too small, long-term storage stability at room temperature may not be obtained; if the amount of the reaction control agent is too large, curing may be slowed down and sufficient curing properties may not be obtained.

[0199] When the component (G) is added to the composition of the present invention, the amount thereof used is preferably in the range of 0.01 to 0.5 parts by mass, particularly preferably in the range of 0.02 to 0.3 parts by mass, based on 100 parts by mass of the component (A).

[0200] 〔Other ingredients〕

[0201] In order to improve its practicality, in addition to the above-mentioned components, various compounding agents such as a plasticizer, a viscosity modifier, a toughening agent, an inorganic filler other than the component (D) and the component (E), an adhesion promoter, and a silane coupling agent may be added to the photocurable fluoropolyether elastomer composition as needed. The amount of these additives may be any amount as long as the purpose of the present invention is not impaired and the properties of the composition and the properties of the cured product are not impaired.

[0202] As the plasticizer, viscosity modifier and toughening agent, a polyfluoromonoolefin compound represented by the following formula (3) and / or a linear or branched polyfluoro compound represented by the following formula (4), formula (5) or formula (6) may be used in combination.

[0203] R 3 -(X') aCH=CH2 (3)

[0204] [In formula (3), X' is the same as defined in the compound of formula (1) in component (A), a is 0 or 1, Rf 3 It is a group represented by the following formula (iii).

[0205]

[0206] (In the formula, f1 is an integer greater than 1, preferably an integer from 2 to 100, t is an integer from 1 to 3, and f1 is greater than Rf 1 The sum of the group's p+q (average value) and r, and the sum of u and v should be smaller. )]

[0207] D1-(CF2CF2CF2O) c1 -D2(4)

[0208] (In the formula, D1 and D2 are independently represented by the formula: s F 2s+1 -(s is 0 to 3), c1 is an integer of 1 to 200, preferably an integer of 2 to 100, and is smaller than Rf of the component (A) 1 The sum of the group's p+q (average value) and r, and the sum of u and v should be smaller.)

[0209] D3-O-(CF2O) d1 (CF2CF2O) e1 -D3(5)

[0210] (In the formula, D3 is represented by the formula: C W F 2W+1 -(w is 0 to 3), d1 and e1 are each an integer of 1 to 200, preferably an integer of 1 to 100, and the sum of d1 and e1 is 1 The sum of the group's p+q (average value) and r, and the sum of u and v.

[0211] D3-O-(CF2O) f1 [CF2CF(CF3)O] g1 -D3(6)

[0212] (In the formula, D3 is the same as above, f1 and g1 are integers of 1 to 200, preferably 1 to 100, and the sum of f1 and g1 is the Rf of the component (A) 1 The sum of the p+q (average value) and r of the group, and the sum of u and v is less than )

[0213] Specific examples of the polyfluoromonoene compound represented by the above formula (3) include the following compounds (it should be noted that the following f1' satisfies the requirements of the above f1).

[0214]

[0215] (In the formula, f1' is an integer from 1 to 100.)

[0216] As specific examples of polyfluorinated compounds having straight chains or branches represented by the above formula (4), formula (5) or formula (6), for example, the following compounds can be listed (it should be noted that the sum of c1', d1' and e1' and the sum of f1' and g1' satisfy the requirements of the sum of c1, d1 and e1 and the sum of f1 and g1 respectively.).

[0217] F-(CF2CF2CF2O) c1’ -CF2CF3

[0218] CF3-[(OCF2CF2) e1’ (OCF2) d1’ ]-O-CF3

[0219] CF3-[(OCF(CF3)CF2) g1’ (OCF2) f1’ ]-O-CF3

[0220] (In the formula, c1' is an integer of 1 to 200, d1' is an integer of 1 to 200, e1' is an integer of 1 to 200, d1'+e1'=2 to 200, f1' is an integer of 1 to 200, g1' is an integer of 1 to 200, f1'+g1'=2 to 200.)

[0221] The viscosity (23° C.) of the compounds of the formulae (3) to (6) as measured by a rotational viscometer is preferably in the range of 5 to 100,000 mPa·s for the same reason as for the linear fluoropolyether compound of the formula (1).

[0222] When the compounds of the formulae (3) to (6) are added, the amount thereof is preferably 1 to 300 parts by mass, particularly preferably 50 to 250 parts by mass, based on 100 parts by mass of the component (A) in the photocurable fluoropolyether elastomer composition.

[0223] As inorganic fillers other than component (D) and component (E), reinforcing or quasi-reinforcing fillers such as quartz powder, fused quartz powder, diatomaceous earth, and calcium carbonate; inorganic pigments such as titanium oxide, iron oxide, carbon black, and cobalt aluminate; heat resistance improvers such as iron oxide, carbon black, cerium oxide, cerium hydroxide, zinc carbonate, magnesium carbonate, and manganese carbonate; thermal conductivity imparting agents such as aluminum oxide, boron nitride, silicon carbide, and metal powder; and conductivity imparting agents such as carbon black, silver powder, and conductive zinc white.

[0224] In addition, as adhesion promoters other than the above-mentioned component (F), adhesion promoters such as titanate, silane coupling agents such as silanes containing epoxy groups such as 3-(glycidyloxy)propyltrimethoxysilane, 3-(glycidyloxy)propyltriethoxysilane, 3-(glycidyloxy)propylmethyldimethoxysilane, and 3-(glycidyloxy)propylmethyldiethoxysilane, etc., can be added.

[0225] By using a mixing device such as a planetary mixer, a Ross mixer, a Hobart mixer, or a kneading device such as a kneader or a three-roll mill as needed, the above-mentioned (A) component to (G) component and any other optional components are uniformly mixed, thereby being able to produce a photocurable fluoropolyether elastomer composition. It should be noted that, with respect to the (D) component and the (E) component, in order to uniformly disperse the (D) component and the (E) component in the (A) component, it is preferred that the (D) component and the (E) component are uniformly mixed with the (A) component in advance to prepare a matrix compound, and then, each matrix compound and the remaining components are mixed. In addition, when manufacturing the composition, in order to remove the air contained in the composition that may be involved during mixing, it is preferred that a degassing operation is performed at the end of the manufacturing process using means such as centrifugal separation.

[0226] Bonding method of photocurable fluoropolyether elastomer composition

[0227] The bonding method of the photocurable fluoropolyether elastomer composition of the present invention (i.e., a method for bonding a cured product of the photocurable fluoropolyether elastomer composition to a substrate surface) comprises the following three steps.

[0228] 1. First, the process of modifying the substrate surface by plasma irradiation

[0229] 2. Next, a step of applying the photocurable fluoropolyether elastomer composition onto the surface-modified substrate and photocuring the composition

[0230] 3. Finally, a step of bonding the fluoroelastomer (cured product) obtained above to a substrate by leaving it to stand for a certain period of time. Each step is described in detail below.

[0231] 1. Process of modifying the substrate surface

[0232] First, the surface of the substrate is modified by plasma irradiation in an atmosphere containing oxygen. The surface modification method of the substrate in the present invention is carried out by plasma irradiation in an atmosphere containing oxygen. It should be noted that the so-called surface modification of the substrate by plasma irradiation is generally considered to refer to the effect of decomposing / cleaning organic matter such as garbage or grease components on metal substrates or inorganic substrates such as glass and ceramics. For substrates made of organic resins, in addition to the above-mentioned cleaning effect, it further has the effect of decomposing the resin surface, giving the surface of the substrate convexity and / or generating polar groups such as carbonyl groups (hydrophilic effect).

[0233] The substrate used in the present invention is not particularly limited, and examples thereof include metals such as iron, aluminum, and stainless steel, glass, ceramics, and synthetic resins such as PPS, PBT, PET, and nylon.

[0234] Furthermore, in order to enhance the effect of surface modification, it is preferred that the surface of the substrate be degreased with an organic solvent or subjected to a pre-baking treatment before the plasma irradiation.

[0235] Plasma treatment method

[0236] Regarding the plasma treatment method used in the present invention, any plasma treatment at atmospheric pressure or low pressure can be used, but the plasma treatment needs to be performed in an atmosphere containing at least oxygen. Therefore, it is preferred to generate plasma in an air atmosphere for surface modification, and it is more preferred to generate plasma in an atmosphere of oxygen-containing gas (such as nitrogen, argon and other inert gases, etc.) for surface modification.

[0237] In the case of atmospheric pressure plasma treatment, the irradiation distance is 3 mm to 10 cm, preferably 5 mm to 5 cm. If the irradiation distance is too short, it is not preferred because it may reduce the workability due to the narrowing of the treatment area or may cause the substrate to deteriorate. If the distance is too long, the modification efficiency may be reduced and the desired modification effect may not be obtained, so it is not preferred.

[0238] In addition, the irradiation time of the atmospheric pressure plasma is 1 to 120 seconds, preferably 5 to 60 seconds. If the irradiation time is shorter than the above, the desired modification effect may not be obtained; on the contrary, if the irradiation time is long, it may lead to reduced workability or degradation of the substrate, so it is not preferred to be outside the above range.

[0239] In the case of low-pressure plasma treatment, 5 to 120 seconds can be performed under high-frequency output conditions of 50 to 500 W, and preferably 10 to 60 seconds can be performed under high-frequency output conditions of 100 to 300 W. In the case of irradiation with a lower output and a shorter time than the above setting, the desired modification effect may not be obtained; in the case of irradiation with a higher output and a longer time than the above setting, it may lead to a decrease in workability or degradation of the substrate, etc. Therefore, outside the above range is not preferred.

[0240] 2. Step of photocuring the photocurable fluoropolyether elastomer

[0241] Next, the photocurable fluoropolyether elastomer composition is applied onto the surface of the surface-modified substrate obtained in the above step 1, and the composition is cured by irradiating light to obtain a fluorinated elastomer (cured product).

[0242] Here, during curing, the light irradiated is preferably near ultraviolet light (hereinafter, sometimes simply described as ultraviolet light). In particular, the maximum peak wavelength in the emission spectrum is in the region of 300 to 400 nm, and the irradiance of each wavelength in the wavelength region shorter than 300 nm is 5% or less of the irradiance of the maximum peak wavelength, preferably 1% or less, more preferably 0.1% or less, that is, the closer to 0, the more preferable. If light having a wavelength in the wavelength region shorter than 300 nm and an irradiance greater than 5% of the irradiance of the maximum peak wavelength is irradiated, decomposition of the polymer end group and / or decomposition of a part of the catalyst will occur, and a satisfactory cured product may not be obtained.

[0243] The type of active light used to cure the photocurable fluoropolyether elastomer composition to obtain the fluorinated elastomer is not particularly limited, but ultraviolet rays of the above-mentioned wavelengths are preferred. In order to obtain good curability, the ultraviolet irradiation amount (illuminance) is preferably 1000 to 50000 mJ / cm as the cumulative light amount. 2 , more preferably 2000 to 20000 mJ / cm 2 , more preferably 5000 to 10000 mJ / cm 2 The ultraviolet radiation (illuminance) is less than 1000~50000mJ / cm 2 At the lower limit of the range, sufficient energy for activating the photoactive hydrosilylation catalyst in the composition may not be obtained, resulting in failure to obtain a cured product (fluoroelastomer) having sufficient physical properties (mechanical strength, etc.); on the other hand, when the ultraviolet irradiation amount (illuminance) exceeds the above 1000 to 50000 mJ / cm 2If the amount is above the upper limit of the range, the composition may be irradiated with energy exceeding the required amount, thereby causing decomposition of the polymer terminal groups and / or deactivation of part of the catalyst, and thus failing to obtain a satisfactory cured product.

[0244] Ultraviolet irradiation may be light having a plurality of luminous spectra or light having a single luminous spectrum. In addition, a single luminous spectrum may also have a wide spectrum in the region of 300 to 400 nm. Light having a single luminous spectrum is light having a peak in the range of 300 to 400 nm, preferably having a peak (i.e., maximum peak wavelength) in the range of 350 to 380 nm. As a light source for irradiating such light, ultraviolet light-emitting semiconductor element light sources such as ultraviolet light-emitting diodes (ultraviolet LEDs) and ultraviolet light-emitting semiconductor lasers may be cited.

[0245] As light sources for irradiating light having multiple emission spectra, there can be listed lamps such as metal halide lamps, xenon lamps, carbon arc lamps, chemical lamps, sodium lamps, low-pressure mercury lamps, high-pressure mercury lamps, and ultra-high-pressure mercury lamps, gas lasers such as nitrogen, liquid lasers of organic pigment solutions, solid lasers containing rare earth ions in inorganic single crystals, and the like.

[0246] When the light has a peak in a wavelength region shorter than 300nm in the emission spectrum, or when there is a wavelength having an irradiance greater than 5% of the irradiance of the maximum peak wavelength in the emission spectrum in a wavelength region shorter than 300nm (for example, when the emission spectrum is wide over a wide wavelength region), it is preferred that the light of wavelengths in a wavelength region shorter than 300nm be removed by a filter. Thus, the irradiance of each wavelength in a wavelength region shorter than 300nm can be adjusted to less than 5% of the irradiance of the maximum peak wavelength, preferably less than 1%, more preferably less than 0.1%, and further preferably 0%. It should be noted that when there are multiple peaks in the wavelength region of 300nm to 400nm in the emission spectrum, the peak wavelength showing the maximum absorbance therein is taken as the maximum peak wavelength. There is no particular limitation on the filter, as long as it can remove wavelengths shorter than 300nm, and a known filter can be used. For example, a 365nm bandpass filter can be used. It should also be noted that the illuminance and spectral distribution of ultraviolet rays can be measured using a spectroradiometer, such as USR-45D (USHIO Motor).

[0247] The light irradiation device is not particularly limited, and for example, a spot irradiation device, a surface irradiation device, a stripe irradiation device, a conveyor irradiation device, or the like can be used.

[0248] When curing the photocurable fluoropolyether elastomer composition, the light irradiation time is, for example, 1 to 300 seconds, preferably 10 to 200 seconds, more preferably 30 to 150 seconds, depending on the illumination of the light used, and the photocurable composition loses fluidity 1 to 60 minutes after the light irradiation, particularly 5 to 30 minutes after the light irradiation, to obtain a rubber elastic body.

[0249] In addition, the ambient temperature during photocuring has an impact on the curing time. That is, under low temperature conditions, the time required to complete the curing is longer, and conversely, under high temperature conditions, the time required to complete the curing is shorter. In the sense of making full use of the characteristics of photocuring, the ambient temperature during curing is preferably 10 to 120°C. If the temperature is lower than the lower limit of the above temperature range, it takes a long time to cure, so it is not preferred from the perspective of workability; on the contrary, if the temperature is higher than the upper limit of the above temperature range, it may cause thermal degradation (thermal deformation / thermal discoloration) depending on the substrate, so it is not preferred.

[0250] In the present invention, the method of applying the photocurable fluoropolyether elastomer composition to the substrate subjected to surface modification treatment may be a method in which the composition is applied to the substrate and then cured by light irradiation by the above method. Alternatively, the composition may be applied to the substrate after being separately irradiated with light until it is cured.

[0251] Here, there is no particular limitation on the coating method of the composition, and examples thereof include potting, bar coater coating, roller coating, spin coating, etc. In addition, there is no particular limitation on the coating amount of the composition, but the coating thickness is preferably 1 μm to 10 mm, and particularly preferably 10 μm to 5 mm.

[0252] 3. Fluoroelastomer bonding process

[0253] As described above, the substrate and the fluoroelastomer (cured product) can be bonded by leaving the fluoroelastomer (cured product) on the substrate to stand for a predetermined time or longer. If the substrate is not left to stand for a sufficient time, a cured product having rubber elasticity can be obtained, but sometimes the adhesion between the cured product and the substrate becomes insufficient.

[0254] At this time, the ambient temperature for standing still needs to be 10 to 120° C. If it is lower than the lower limit of the temperature range, it may take longer to express the adhesiveness; on the contrary, if it is higher than the upper limit of the temperature range, it may cause thermal degradation (thermal deformation / thermal discoloration) depending on the substrate, so it is not preferred.

[0255] The time for standing is not particularly limited because it is affected by the ambient temperature and can be appropriately selected, but is preferably 5 minutes to 7 days, more preferably 10 minutes to 48 hours, and particularly preferably 6 hours to 48 hours.

[0256] The bonding method of the present invention is useful as a method for bonding a cured product of a photocurable fluoropolyether elastomer composition to automobile-related parts, various electric / electronic parts, etc. For example, it is useful as an adhesive sealant, protective coating agent, potting agent for various pressure sensors, gas concentration detectors, temperature sensors, etc. used in automobile control systems, as well as a protective encapsulant for sensors exposed to various gases, warm water, chemicals, etc., an adhesive for inkjet printers, an adhesive / encapsulant for print heads, a coating agent for rollers or belts of laser printers or copying devices, an adhesive sealant, coating agent, potting agent for various circuit boards, etc., for bonding a cured product of a photocurable fluoropolyether elastomer composition to these parts.

[0257] [Example]

[0258] The present invention is specifically described below by the preparation examples, embodiments and comparative examples, but the present invention is not limited to the following examples. It should be noted that the parts in the following examples are expressed as parts by mass. Me represents a methyl group, and Vi represents a vinyl group. In addition, the molecular weight is expressed as a number average molecular weight converted to polystyrene in GPC analysis. The viscosity is expressed as a measured value at 23°C (based on JIS K7117-1 standard).

[0259] Preparation of Matrix Compound A

[0260] 100 parts of a polymer represented by the following formula (7) (viscosity 11000 mPa·s, number average molecular weight 17500, vinyl content 0.012 mol / 100 g) were placed in a planetary mixer, and while the internal temperature was maintained at 50 to 100° C., 10 parts of fumed silica (BET specific surface area 110 m 2 / g). Then, the heating was stopped and kneading was carried out for 1 hour under reduced pressure (gauge pressure; -0.093MPa). Then, the heating device was heated while kneading, and after the internal temperature reached 130°C and was maintained at 130 to 160°C, heat treatment was carried out for 1 hour under reduced pressure (gauge pressure; -0.093MPa). Then, after the contents were cooled to below 40°C, the contents were taken out and processed twice by a three-roll mill to obtain a matrix compound A (matrix A).

[0261]

[0262] Preparation of Matrix Compound B

[0263] 100 parts of the polymer represented by the above formula (7) were charged into a planetary mixer, and while the internal temperature was maintained at 50 to 100°C, 10 parts of zeolite (Zeoal Z4A-005 manufactured by Nakamura Superhard Co., Ltd., Japan, with an average primary particle size of 50 nm) were added in portions. Then, the heating was stopped, and kneading was carried out for 1 hour under reduced pressure conditions (gauge pressure; -0.093 MPa). Then, the heating device was heated while kneading, and after the internal temperature reached 130°C, it was maintained at 130 to 160°C, and heat treatment was carried out for 1 hour under reduced pressure conditions (gauge pressure; -0.093 MPa). Then, after the contents were cooled to below 40°C, the contents were taken out and processed twice through a three-roll mill to obtain a matrix compound B (matrix B).

[0264] Preparation of Matrix Compound C

[0265] 100 parts of the polymer represented by the above formula (7) were charged into a planetary mixer, and while the internal temperature was maintained at 50 to 100°C, 10 parts of molecular sieve powder 3A (porous zeolite powder manufactured by UNION SHOWA KK, with an average primary particle size of 1800 nm) were added in portions. Then, the heating was stopped, and kneading was carried out for 1 hour under reduced pressure conditions (gauge pressure; -0.093 MPa). Then, the device was heated while kneading, and after the internal temperature reached 130°C, it was maintained at 130 to 160°C, and heat treatment was carried out for 1 hour under reduced pressure conditions (gauge pressure; -0.093 MPa). Then, after the contents were cooled to below 40°C, the contents were taken out and processed twice through a three-roll mill to obtain a matrix compound C (matrix C).

[0266] Preparation of Matrix Compound D

[0267] 100 parts of the polymer represented by the above formula (7) were charged into a planetary mixer, and while the internal temperature was maintained at 50 to 100°C, 10 parts of porous silica beads (SB-300 manufactured by Miyoshi Chemicals Co., Ltd., Japan, with an average primary particle size of 5 μm) were added in portions. Then, the heating was stopped, and kneading was carried out for 1 hour under reduced pressure (gauge pressure; -0.093 MPa). Then, the heating device was heated while kneading, and after the internal temperature reached 130°C, it was maintained at 130 to 160°C, and heat treatment was carried out for 1 hour under reduced pressure (gauge pressure; -0.093 MPa). Then, after the contents were cooled to below 40°C, the contents were taken out and processed twice through a three-roll mill to obtain a matrix compound D (matrix D).

[0268] Preparation of photocurable fluoropolyether elastomer composition

[0269] [Preparation Example 1]

[0270] 55 parts of the above-mentioned base compound A and 55 parts of the above-mentioned base compound B were charged into a planetary mixer and mixed until uniform. Then, 0.055 parts of a 1,3-bis(trifluoromethyl)benzene solution of (methylcyclopentadienyl)trimethylplatinum (IV) (platinum concentration 3.0 mass%) and 0.064 parts of a toluene solution of 1-ethynyl-1-hydroxycyclohexane (5.0 mass%) were added to the above-mentioned mixed compounds and mixed until uniform. Next, 0.25 parts of fluorinated organohydrogen polysiloxane (Si-H group content: 0.0050 mol / g) represented by the following formula (9), 1.96 parts of fluorinated organohydrogen polysiloxane (Si-H group content: 0.0072 mol / g) represented by the following formula (10), 2.2 parts of an adhesion-imparting agent represented by the following formula (12), and 0.1 parts of an epoxy-containing silane compound represented by the following formula (13) were added in sequence and mixed until uniform. Then, a degassing operation was performed by a centrifuge to prepare composition A.

[0271]

[0272]

[0273] [Preparation Example 2]

[0274] 55 parts of the matrix compound A, 33 parts of the matrix compound B and 20 parts of the polymer represented by the above formula (7) were placed in a planetary mixer and mixed until uniform. Then, 0.054 parts of a 1,3-bis(trifluoromethyl)benzene solution of (methylcyclopentadienyl)trimethylplatinum (IV) (platinum concentration 3.0 mass %) and 0.063 parts of a toluene solution of 1-ethynyl-1-hydroxycyclohexane (5.0 mass %) were added to the above mixed compounds and mixed until uniform. Next, 1.23 parts of fluorinated organohydrogen polysiloxane (Si-H group content: 0.0050 mol / g) represented by the above formula (9), 1.20 parts of fluorinated organohydrogen polysiloxane (Si-H group content: 0.0072 mol / g) represented by the above formula (10), 2.2 parts of an adhesive agent represented by the above formula (12), and 0.1 parts of an epoxy-containing silane compound represented by the above formula (13) were added in sequence and mixed until uniform. Then, a degassing operation was performed by a centrifuge to prepare composition B.

[0275] [Preparation Example 3]

[0276] 55 parts of the matrix compound A, 11 parts of the matrix compound B and 40 parts of the polymer represented by the above formula (7) were charged into a planetary mixer and mixed until uniform. The following steps of adding and mixing the components were the same as in Preparation Example 1, thereby preparing Composition C.

[0277] [Preparation Example 4]

[0278] 55 parts of the matrix compound B and 50 parts of the polymer represented by the above formula (7) were charged into a planetary mixer and mixed until uniform. The following steps of adding and mixing components were the same as in Preparation Example 1, thereby preparing Composition D.

[0279] [Preparation Example 5]

[0280] 55 parts of the base compound A and 55 parts of the base compound C were charged into a planetary mixer and mixed until uniform. The following steps of adding and mixing components were the same as in Preparation Example 1, thereby preparing Composition E.

[0281] [Preparation Example 6]

[0282] 55 parts of the matrix compound A and 50 parts of the polymer represented by the above formula (7) were charged into a planetary mixer and mixed until uniform. The following steps of adding and mixing components were the same as in Preparation Example 1, thereby preparing Composition F.

[0283] [Preparation Example 7]

[0284] 88 parts of the base compound A and 20 parts of the polymer represented by the above formula (7) were charged into a planetary mixer and mixed until uniform. The following steps of adding and mixing components were the same as in Preparation Example 1, thereby preparing Composition G.

[0285] [Preparation Example 8]

[0286] 55 parts of the base compound A and 55 parts of the base compound D were charged into a planetary mixer and mixed until uniform. The following steps of adding and mixing components were the same as in Preparation Example 1, thereby preparing Composition H.

[0287] [Examples 1 to 5 and Comparative Examples 1 to 3]

[0288] Viscosity of each composition

[0289] The viscosity of the compositions of Examples 1 to 5 and Comparative Examples 1 to 3 (the above-mentioned compositions A to H) was measured at 23° C. in accordance with JIS K7117-1. The results are shown in Tables 1 and 2.

[0290] Curing test of light-cured materials

[0291] After the obtained composition was filled in a cylindrical container, the composition was extruded onto a tetrafluoroethylene flat plate (50 mm × 50 mm × 2 mm) and coated with a rod coater to a composition layer thickness of 1 mm. The tetrafluoroethylene flat plate coated with the composition was irradiated with light using a UV-LED irradiator (365 nm type, manufactured by CCS Inc., Japan). At this time, the wavelength was 365 nm, 100 mW / cm 2 The samples were irradiated at 23°C for 90 seconds under UV illumination conditions. After standing at 23°C for 24 hours, the surface state was observed, and the samples that were not tack-free and cured were evaluated as O, and the samples that were tack-free and not cured were evaluated as ×. The results are shown in Tables 1 and 2.

[0292] Adhesion test of light-cured materials

[0293] Next, the test plates of the various two groups of adherends (50mm×25mm) recorded in Tables 1 and 2 were degreased with ethanol and then plasma treated using a low-pressure plasma irradiation device (Yamato Scientific Co., Ltd. plasma dry cleaning machine (PLASMA DRY CLEANER), O2 / Ar=80cc / 20cc, RF output: 250W, irradiation time: 30 seconds). After the test plate was plasma treated, 2g of each composition was applied to the adherend on one side, and light irradiation was performed in the same manner as above. Then, the composition layer with a thickness of 80μm was overlapped on the adherend on the other side in a manner that each end overlapped 10mm, and then it was left to stand for 24 hours at 23°C to prepare a bonding test piece. Next, according to the JIS K6850 standard, a tensile shear bonding strength test (tensile speed 50mm / minute) was performed to evaluate the tensile shear bonding strength (MPa) and cohesive failure rate (area%). The results are shown in Tables 1 and 2.

[0294] Foaming test of light-cured materials

[0295] After degreasing the surface of a glass plate (50mm×50mm×1mm) with ethanol, 1g of each composition was applied to the center of the glass plate and irradiated with light in the same manner as above. After that, a 1mm thick metal plate was placed 10mm on both sides of the glass plate, and other glass plates were placed from above to sandwich each composition layer. In this state, and left to stand at 23°C for 2 hours, the resin layer was evaluated as O if there was no foaming, and the resin layer was evaluated as × even if one foaming was confirmed. The results are shown in Tables 1 and 2.

[0296] Table 1

[0297]

[0298] Table 2

[0299]

[0300] From the results in Tables 1 and 2, it can be confirmed that in the examples of the present invention, if the photocurable fluoropolyether elastomer composition contains zeolite, no bubbles are generated in the fluoroelastomer resin even if it is photocured, and it can be well bonded to various substrates under low temperature conditions and in a short time.

Claims

1. Use for suppressing the generation of hydrogen in a cured product due to the dehydrogenation reaction of hydrogen atoms bonded to silicon atoms described below during curing after UV irradiation, in a cured product obtained by curing a photocurable fluoropolyether elastomer composition by UV irradiation, The photocurable fluoropolyether elastomer composition comprises: (A) a linear polyfluorinated compound having two or more alkenyl groups in one molecule and having a perfluoropolyether structure in the main chain, (B) a fluorinated organohydrogenpolysiloxane having two or more hydrogen atoms bonded to silicon atoms in one molecule, (C) a photoactive hydrosilylation catalyst, and (D) Zeolite having an average primary particle size of 30 μm or less.

2. The use according to claim 1, wherein The component (B) is contained in an amount of 0.5 to 3.0 mol of hydrogen atoms bonded to silicon atoms in the component (B) per 1 mol of alkenyl groups in the component (A).

3. The use according to claim 1, wherein The (D) component is contained in an amount of 0.1 to 20 parts by mass based on 100 parts by mass of the (A) component.

4. A cured product of a photocurable fluoropolyether elastomer composition, which is a cured product obtained by curing the photocurable fluoropolyether elastomer composition by UV irradiation, The photocurable fluoropolyether elastomer composition comprises: (A) a linear polyfluorinated compound having two or more alkenyl groups in one molecule and having a perfluoropolyether structure in the main chain, (B) a fluorinated organohydrogenpolysiloxane having two or more hydrogen atoms bonded to silicon atoms in one molecule, (C) a photoactive hydrosilylation catalyst, and (D) zeolite having an average primary particle size of 30 μm or less, The solidified material does not foam under the following conditions: Foaming test of cured product After degreasing the surface of a glass plate (50 mm×50 mm×1 mm) with ethanol, 1 g of the photocurable fluoropolyether elastomer composition was applied to the center of the glass plate and irradiated with a UV-LED irradiator (365 nm type, manufactured by CCS Inc., Japan) at a wavelength of 365 nm and 100 mW / cm 2 The glass plate was exposed to UV light for 90 seconds at 23°C, and then 1 mm thick metal plates were placed at 10 mm on both sides of the glass plate. Other glass plates were placed on top to sandwich the composition layer. In this state, the glass plate was allowed to stand at 23°C for 2 hours, and the solidified material without foaming was taken as the solidified material without foaming.

5. The cured product of the photocurable fluoropolyether elastomer composition according to claim 4, wherein The component (B) is contained in an amount of 0.5 to 3.0 mol of hydrogen atoms bonded to silicon atoms in the component (B) per 1 mol of alkenyl groups in the component (A).

6. The cured product of the photocurable fluoropolyether elastomer composition according to claim 4, wherein The (D) component is contained in an amount of 0.1 to 20 parts by mass based on 100 parts by mass of the (A) component.

7. An automobile-related part comprising a cured product of the photocurable fluoropolyether elastomer composition according to any one of claims 4 to 6.

8. An electric or electronic component comprising a cured product of the photocurable fluoropolyether elastomer composition according to any one of claims 4 to 6.

Citation Information

Patent Citations

  • Photocurable fluoropolyether rubber composition and rubber material

    JP2007106785A

  • Photocurable fluoropolyether-based rubber composition, cured product thereof, and method of curing the same

    JP2016145354A